Singhasari Tourism Special Economic Zone: Can it Survive in Today's World Economy? - Anisah, Azmi Listya; Katharina, Riris; Ma'rifah, Diana; Apriani, Tini; Syah, Ardy Firman; Sacipto, Rian; Fadhilah, Hasna Azmi; Navisa, Fitria Dewi (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
Indonesia is developing a Special Economic Zone (SEZ) in the tourism sector with Singhasari being the only SEZ that emphasizes cultural and historical heritage tourism. However, until the end of November 2022, Singhasari SEZ has not demonstrated significant success. This article explores the reason behind the Singhasari SEZ’s relative lack of success compared to other SEZs, based on the results of research conducted in November 2022. It examines the institutional governance of the Singhasari SEZ since its inception and analyzes the obstacles encountered, utilizing the theory of the three main pillars of SEZ success. The research employed a qualitative approach utilizing a case study method. Data collection was conducted through observation, interviews, and literature study. The findings reveal that the Singhasari SEZ is managed according to existing regulations with Intelegensia Grahatama, Ltd. as a Development and Management Business Entity of the Singhasari SEZ. A significant obstacle identified from a strategic perspective was the initial decision to focus on a historic location for tourism, a choice that lost its relevance during the COVID-19 pandemic. However, the efforts to transition the Singhasari SEZ’s focus from tourism to digital education demonstrate its strategic dynamism. In terms of strategic implementation, the Singhasari SEZ requires assistance from the Central Government regarding infrastructure development to achieve its objectives. The theoretical implication of this research is that it adds community actors to SEZ institutions. The allocation of special funds for infrastructure development in each approved SEZ as well as the increase of involvement of private and community actors in various SEZ activities are the policy implications of this research.